Novel platinum bipolar electrode for irreversible electroporation in prostate cancer: preclinical study in the beagle prostate - Bumjin Lim (Nature Portfolio, 2021)
Abstract The exposure of the prostate to high electric field strength during irreversible electroporation (IRE) has been extensively investigated. Multiple monopolar electrodes, however, have risks of organ piercing and bleeding when placing electrodes. A novel bipolar electrode made of pure platinum and stainless steel was developed for prostate cancer ablation. Voltages of 500 and 700 V were applied to the beagle prostate with this electrode to evaluate ablated tissues and their characteristics. IRE procedures were technically successful in all dogs without procedure-related complications. The current that flowed through the anode and cathode while applying 500 and 700 V were 1.75 ± 0.25 A and 2.22 ± 0.35 A, respectively. TUNEL assays showed that the estimated ablated areas when applying 500 and 700 V were 0.78 cm2 and 1.21 cm2, respectively. The minimum electric field strength threshold required for induction of IRE was 800 V/cm. The platinum electrode was resistant to corrosion. The IRE procedure for beagle prostates using a single bipolar electrode was technically feasible and safe. The novel bipolar electrode has great potential for treating human prostate cancer with fewer IRE-related complications.